Laminate veneers: A review and clinical case - Archangelo, Carlos Marcelo [UNESP]; Rocha, Eduardo Passos [UNESP]; Martin, Manoel [UNESP]; Anchieta, Rodolfo Bruniera [UNESP]; Sundfeld, Renato Herman [UNESP] (My University, 2013)
The laminate veneers are great choice for rehabilitation for anterior segment of the mouth. Actually, due the employment of dental cements and bonding to dentin, the uses of laminate veneers is an effective and conservative treatment, showing a high rate success rate. This paper presents a clinical case of 50 years old male, J.C.H, who have a chief complaint of an unattractive smile. After the diagnosis and planning, 10 laminate veneers were placed from the second bicuspid (15) to the second bicuspid (25). The correct indication of laminate veneers allows restorations with appropriate esthetic and patient's satisfaction with immediate effect on quality of life.
Keywords: Dental aesthetics; Dental ceramic; Laminate veneer